The Three Failed Promises of ObamaCare. - Troy, Tevi (Commentary, 2013)
The article discusses purported problems with the U.S. Affordable Care Act (ObamaCare). Topics include the law's ability to provide universal health insurance coverage in the U.S., its effectiveness in controlling health insurance premiums as an aspect of health care costs, and the impact of the law on previously existing health insurance plans.